Identification of the O/ME-SA/Ind-2001e Sublineage of Foot-and-Mouth Disease Virus in Cambodia - Ryoo, Soyoon; Lee, HyunJi; Lim, Da-Rae; Lee, Jung-Won; Bunnary, Seng; Tum, Sothyra; Lee, Dong Sook; Hwang, Hyeonwoo; Jeong, SomGyeol; Nah, JinJu; Ku, Bok Kyung; Kim, Jae-Myung; et al. (Frontiers in Veterinary Science, 2021)
Foot-and-mouth (FMD) is endemic in Cambodia with numerous outbreaks in cattle, pigs and other susceptible animal species reported every year. Historically, these outbreaks were caused by the FMD virus (FMDV) of serotype O PanAsia and Mya-98 lineages and serotype A Sea-97 lineage. However, the trans-pool movement of FMDV between inter-pool regions or countries throughout FMD endemic regions has raised concerns regarding infection with the new genotype or serotype of FMDV in Cambodia. In this study, 19 sequences of VP1 coding region obtained from 33 clinical samples collected from FMDV-affected cattle farms in Cambodia during January to March 2019 were genetically characterized to identify the genotypes/lineages of FMDV. Phylogenetic analysis of VP1 coding sequences revealed that recent field viruses belonged to O/ME-SA/Ind-2001e (15.8%), O/ME-SA/PanAsia (52.7%), and A/ASIA/Sea-97 (31.5%). Besides, the field viruses of O/ME-SA/Ind-2001e in Cambodia showed 93.5–96.8% identity with the VP1 coding sequences of the same sublineage viruses from pool 1 and 2 surrounding Cambodia. This is the first report of O/ME-SA/Ind-2001e infection in Cambodia, suggesting that the trans-pool movement of the new genotype should be closely monitored for efficient control of FMD.